Perancangan Aplikasi Pendaftaran Online Pasien Rawat Jalan Berbasis Android Di Rumah Sakit Santa Elisabeth - Katarina Yuni Saptariningsih; Trismianto Asmo Sutrisno; Sri Sugiarsi (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Nowadays, there are so many tools to convey and to receive all informations. One of the tools is a smartphone. One of the mobile devices that is widely used today is an Android-based smartphone. So far, information regarding doctor's practice schedules and other information related to hospitals has only been through social media, Instagram and websites. Besides that, patient registration for appointments with specialist doctors have been done through a telephone and WhatsApp which make so many patients complain about the slow response. The goal or the aims of this research is to design an online registration system for outpatients at Santa Elisabeth Hospital. This type of research is a type of qualitative descriptive research. This application was built using the PHP application program and uses a MySQL database. The design result is an Android-based online patient registration application, which is expected to help admins (registration officers) and users (patients) register effectively and efficiently. Keywords: patient registration, application, android